Theatre, community, and civic engagement in Jacobean London - Bayer, Mark, 1973- (Studies in theatre history and culture., 2011)
Taking to heart Thomas Heywood's claim that plays "persuade men to humanity and good life, instruct them in civility and good manners, showing them the fruits of honesty, and the end of villainy," Mark Bayer's captivating new study argues that the early modern London theatre was an important community institution whose influence extended far beyond its economic, religious, educational, and entertainment contributions. Bayer concentrates not on the theatres where Shakespeare's plays were performed but on two important amphitheatres, the Fortune and the Red Bull, t.